Studies on the role of 5-HT2A and 5-HT2C receptor antagonist and effects of co-administration of Fluoxetines in regulating generalized seizures in albino rats - Vasant R Chavan; RS Wali; RD Totad (Al Ameen Medical College, 2010)
Introduction: Epilepsy is due to imbalance between inhibitory & excitatory neurotransmitter release at synaptic level in brain such as GABA, Serotonin, Glutamate and nor epinephrine. Recently there are few reports suggesting that, 5-HT1A receptor antagonist with co-administration of fluoxetine has shown anticonvulsant activity. The present study is undertaken to evaluate the action of 5-HT2A/2C mediated anticonvulsant action of Trazodone in MES (Maximum Electro Shock) model in albino rats. Materials & Methods: Fifty albino rats of 200-250 gms of either sex were divided into five groups each of 10 rats(n=10), Group-I received distil water 0.5ml oral, Group -II- received sodium valproate - 200mg/kg bw intra peritoneal(i.p.)acted as positive control, Group -III- received Trazodone 54mg/bw, orally Group- IV- received sub-anticonvulsant dose of Fluoxetine 6mg/kg/bw i.p. Group- V- received Trazodone 54mg/kg/bw and Fluoxetine 6mg/kg bw. Subsequently all groups were subjected for MES. The results were analyzed by calculating the mean duration of convulsions & absence of HLE and comparison was done by student't' test. Results: The present study revealed that sodium valproate showed 100% protection against MES as compared to negative control,(P<0.05). Trazodone showed 40% protection against MES& decrease in the duration of convulsions by 60%, and Fluoxitine sub-anticonvulsive dose combined with Trazodone 54 mg /kg b.w. has shown 90% protection against MES. The results are parallel to standard drug sodium valproate. Conclusion: Trazodone has exerted anticonvulsant activity, by enhancing 5-HT&NE extra cellular level in brain, and probably potentiated the action of sub anticonvulsive dose of fluoxetine in combination. However, further investigative studies are needed to confirm the potention of trazodone action.